Pricing Strategies for Different Periods During Subsequent Selling Season for Seasonal Products - Junfeng Dong; Beilei Rao; Yu Liu; Li Jiang; Wenxing Lu; Qiang Guo (IEEE Access, 2020)
This study applies a two-period pricing model to investigate the optimal pricing strategy for different periods during the subsequent selling season for seasonal products. The model assumes that the market is populated by two types of consumers, namely, myopic and strategic, and analyzes three optimal pricing strategies: one price (OP), preannounced slash price (PSP), and preannounced small price reduction (PSPR). Several propositions are derived by comparing these three strategies. Results show that the PSP strategy is superior to PSPR and OP strategies only when certain conditions are satisfied. Otherwise, the OP or the PSPR is consistently superior to the PSP. When retailers adopt a markdown price, they should reduce the price early to ensure a long second period. Finally, this study provides several numerical examples to illustrate the propositions derived from the theoretical analysis.